GIS in soil survey and soil mapping - Ameti, Perparim; Ajvazi, Besim (Geodesy and Cartography, 2021)
The main goal of this paper is to present a methodology for land evaluation by supporting decision-makers with reliable information for the land-use planning process. One of the focuses of this paper is given to the survey process and interpretation between soil survey, soil survey interpretation, and physical land evaluation. Such processes are realized using mobile mapping tools with integrated Global Position Systems (GPS) and Geographic Information Systems (GIS). Both have increased the efficiency of data communication technologies by enabling real-time communication between people located in the field and office as well. For the soil classification as a key component of soil surveys is used World Reference Base (WRB) for Soil Resources. This is a common tool to summarize the wealth of information from soil profiles for the purpose of land evaluation. The final results showed a soil classification map. Such results are derived from many activities, since it includes a preliminary land evaluation, field soil survey with auger holes and profiles as well. This methodology is used for the first time in the selected study area.